Heat transfer inspection of nano-encapsulated phase change materials inside a Γ-shaped enclosure influenced by magnetic field - Fereidooni, Jalil (Journal of magnetism and magnetic materials, 2022)
•Heat transfer inspection of NEPCMs inside a Γ-shaped cavity is carried out.•The Γ-shaped enclosure with the heat flux boundary condition is supposed to be impacted by magnetic field.•The Navier-Stokes equations under the expressed boundary conditions may be solve utilizing finite element method. Nano-Encapsulated phase change materials (NEPCMs) made of shell and a core are new tools used in modern devices such as batteries and solar systems which enhance the cooling behavior of the flow. The written paper analyzes natural convection of the NEPCMs in a Γ-shaped cavity with magnetic field’s impact. The Navier-Stokes equations under the expressed boundary conditions may be solve utilizing FEM. The effect of Rayleigh number (104–106), Nano particle’s concentration (0.01–0.05), Stefan number (0.1–0.9), Hartmann number (0–20), and non-dimensional fusion temperature (0.05–0.1) on the contours of the temperature, velocity, streamline, Cr, and the average Nusselt number are presented. The results divulge that an escalation in Ha from 0 to 20, will reduce the Nuavg up to 17%; however, increasing the nanoparticle concentration will enhance the Nuavg by 26%. This study is applicable in the cooling process of modern batteries and solar-hydrogen components.